Connectors for electronic equipment. Printed board connectors with assessed quality. Detail specification for shielded two-part connectors having a basic grid of 2, 0 mm, fixed part with solder and press-in terminations for printed boards, free part with non-accessible insulation displacement and crimp terminations Part 4-107, (26th November 2001) - British Standards Institution,
No abstract available